NEWLY FOUND DOCUMENTS CONCERNING THE DECISION OF THE BULGARIAN OLYMPIC COMMITTEE ABOUT THE OLYMPIC TORCH RELAY THROUGH BULGARIA IN 1972 - Emilia Vitanova (Journal of Applied Sports Sciences)
The Munich Olympic Games in 1972 were organized and held in the atmosphere of political and ideological controversies, which directly affected the organization and the Olympic Torch Relay along the route Olympia – Munich. This article aims to present newly found evidence about Bulgaria’s participation in planning the overall route of the Olympic Torch Relay across the country. The manuscript includes various documents and scientific and popular publications systematized through content analysis, comparative analysis, and critical analysis. In the course of the research, we also found 32 articles in periodicals. We researched some books and publications by foreign and Bulgarian authors, documents preserved in the regional libraries, the central state archive, the regional archives, and the archives of the Bulgarian Union for Physical Culture and Sport (BUPCS) and “Bulgarian Photography”. The research traced the difficulties and influences making the Bulgarian Olympic Committee (BOC) doubtful about the organization of the Olympic Torch Relay. On the basis of the newly found documents, we can have a clearer view of the political and ideological influences on BOC determining the decision on this matter.